IMPLEMENTASI MANAJEMEN ASET DALAM PENGELOLAAN TAMAN HUTAN RAYA SULTAN ADAM DI KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - , Sindy Pramitasari, Prof. Dr. Iswardono Sardjono Permono, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to and analyze the effect of independent variable: Vegetation Resource Management, Resource Management, Community Framework, Community Education, Legal Audit, and Financing on Implementation of Asset Management. This study uses primary data obtained from questionnaires distributed to employees and decision makers of the Forest Agency Tahura Sultan Adam, South Kalimantan. The analytical method used is regression analysis that will show the effect of independent variables on the dependent variables. The results indicates the implementation of asset management on Tahura Adam Sultan, South Kalimantan was quite decent, but still there are deficiencies that needs attention from the authorities. Hypothesis testing concluded only three independent variables that significantly influence the asset management in Tahura Sultan adam: community framework (hypothesis 2), resource management (hypothesis 3), and funding (hypothesis 5). meanwhile the other are not significant: vegetation resource management (hypothesis 1), community education (hypothesis 4) and legal audit (hypothesis 6), but in simultaneously testing shows all independent variables are significantly influence the implementation of asset management Tahura Sultan Adam, South Kalimantan.